(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Hand fracture management remains complex, with treatment approaches varying based on fracture type, patient characteristics, and healthcare system constraints. Objectives: This retrospective study aimed to determine the effectiveness of the lace method of osteosynthesis in the Kyrgyz Republic and the anesthetic aspects of this method. Materials and Methods: Patients aged 3–71 years with confirmed wrist fractures were divided into two groups: Group 1 (n = 90) underwent cord osteosynthesis, while Group 2 (n = 34) received standard osteosynthesis treatment. The study compared general and administrative indicators of medical care quality between the groups. Results: Domestic injuries were prevalent in all groups and categories, while work injuries had a more stable distribution. Conductor cells accounted for the majority of anesthesia types in both groups (42.20% in Group 1 and 50.00% in Group 2). Group 1 had a higher percentage of local and general anesthesia, whereas Group 2 had a higher content of conductive anesthesia. The age distribution differed between the groups, with Group 1 primarily composed of children of primary and secondary school age, while Group 2 had a higher proportion of adults aged 18–50 years. Conclusion: The findings suggest differences in the composition of anesthesia used and age distribution between the two groups, which may have implications for treatment outcomes and functional activity. Further research is needed to establish standardized guidelines for hand fracture management and to evaluate the effectiveness of the lace method of osteosynthesis in various patient populations.